Psychological Mechanisms of Cultural, Clinical and Individual Transformations of Mentalization - Sokolova, E (KnE Life Sciences, 2018)
The subject of theoretical revision is the impairment of social cognition, which is wellknown in the clinics of borderline personality disorders. Mentalization is understood as a form of social cognition, which allows to perceive, imagine and emotionally relate, make sense and causality of what’s happening in a subjective world – of self and another person. Mentalization supposes integration of contextual factors, material and physical aspects of situation and behavior, as well as inner subjective feelings, beliefs, goals and intentional states as representative motives for a given behavior. In the perspective of the cultural-historical theory and methodology by L.S. Vygotsky a new interpretation is offered for the clinical phenomena of mentalization deficit, an understanding is given for transformation of its structure and functions as a consequence of the person’s loss of interpsychic social connections and disintegration of intrapsychic organization of consciousness, impairment of its systemic structure, narrowing and simplification of cross-functional bonds and intrapsychic “mythology”. In the result of this double destruction of bonds, ontogenetically early and primitive forms of mentalization are «splitting off», isolated and start holding a domineering position in psychic functioning. The process of mentalization regresses to its pre-categorical and cognitive-affective non-differentiated levels and structures (syncretic and complex organization), unfolding involuntarily and unconsciously, lacking meaningful coherence, symbolic mediation and focus for understanding the subjective world – of self and the Other. The unconscious substitution of the psychic picture of the inner world with impulsive actions, hypochondriac and narcissistic fixations, autistic pseudo-mentalization and manipulation is lacking the meaningful and sanguineous dialogue with the Other. The loss of social connections (interpsychic communication), without being mediated by the addressed to the Other speech dialogue is interiorized into the inner “muteness” – the loss of not only understanding of others, but the interruption of meaningful inner and “worded” dialogue with the self, self-understanding. Keywords: mentalization disorders, cultural-historical approach, structure-functional disorganization.